POLITICAL CORRUPTION AND ITS IMPACT ON PUBLIC GOVERNANCE IN POST-APARTHEID SOUTH AFRICA - Sandiso Mahlala; Xolisile Ngumbela; Phumudzo P. Ramolai; Makhura B. Rapanyane; Mahlatse Sevhake (Ayika – Journal of Environment and Politics in Africa, 2026)
Corruption remains one of the most significant governance challenges globally, and sub-Saharan Africa is the lowest-performing region on Transparency International's Corruption Perceptions Index, with an average score of 33 out of 100 for 2024 and 90% of countries in the region scoring below 50 (Corruption Watch, 2025). Political corruption is a persistent challenge in South Africa's public governance. This is evident in numerous corruption scandals involving political elites, public officials, and private businesses that do business with the state. This paper examines various forms of political corruption in post-apartheid South Africa and their impact on government performance, service delivery, economic development, democratic governance, public trust, and the legitimacy of public institutions. This exploration is grounded in principal-agent theory and the agency problem, which illustrate the dynamic relationship between principals' and agents' interests in the public sector. The paper adopts a qualitative approach to synthesize current information on political corruption in South Africa. The results indicate that although political corruption is not a new phenomenon in South Africa, the government struggles to curb it, particularly in public procurement and service delivery. Studying this challenge and understanding its impact on various government functions is crucial. Future research should assess the effectiveness of existing measures to curb political corruption. The paper is significant because it demonstrates the direct effects of political corruption on public services, economic development, and the government's capacity to address citizens' needs.